Assessment of end-tidal carbon dioxide levels in patients presenting to the emergency department with gastrointestinal bleeding - Kılınç, Emine; Karaali, Rezan; Kayalı, Ahmet; Ermete Güler, Ecem; Acar, Hüseyin; Topal, Fatih (The European Research Journal, 2025)
Objectives: Gastrointestinal bleeding is a common condition in emergency departments and can be fatal if diagnosis and treatment are delayed. In this study, we aimed to explore the relationship between end-tidal carbon dioxide (ETCO2) levels and Glasgow Blatchford Score (GBS) and AIMS65 scores, as well as its impact on assessing morbidity and mortality in patients presenting to the emergency department with gastrointestinal bleeding. Methods: The research involved 103 eligible patients diagnosed with gastrointestinal bleeding. ETCO2 measurements were taken on admission and data on hospitalization, GBS/AIMS65 scores, endoscopically detected active bleeding and 30-day mortality were recorded. Statistical analysis was performed on the collected data. Results: When ETCO2 values obtained from the patients were compared according to hospitalization status, GBS score, AIMS65 score, presence of endoscopically detected active bleeding and mortality status; ETCO2 levels were significantly lower in patients with active bleeding, those who died, patients with AIMS65 scores ≥2, and those with GBS scores ≥12 (P<0.05). Conclusions: This study demonstrates that ETCO2 levels are significantly lower in patients with gastrointestinal bleeding, especially in those with active bleeding, high mortality risk, and elevated GBS or AIMS65 scores. ETCO2 may serve as a rapid and practical marker for assessing hypovolemia and clinical status in emergency settings.